Pengaruh Produktivitas, Firm Size dan Maturity Terhadap Peringkat Sukuk Pada Perusahaan Non Keuangan Di Indonesia - Juardi -; Norma Intan Sueno (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
This study aims to determine the effect of productivity, firm size and maturity on sukuk ratings. The dependent variable in this study is sukuk rank while the independent variables are productivity, firm size and maturity. Sukuk rating is measured using an ordinal scale, productivity is measured by total asset turnover, firm size is measured by ln total assets and maturity is measured by dummy variables. The population used in this study are all sukuk issued by non-financial companies which are listed on the Indonesia Stock Exchange for the period of 2016-2018. The sampling method used in this study was purposive sampling. The number of samples in this study were 90 sukuk samples from 10 companies. Data analysis method used to test the hypothesis in this study is the ordinal logistic regression analysis method. The results showed that productivity had a significant positive effect on sukuk ratings, firm size had a significant positive effect on sukuk ratings and maturity had no significant effect on ratings sukuk